The Diffusion of Blockchain Technology for Financial Reporting Functions Seen Through the Lens of Norm Lifecycles - King, Tatiana; Morton, Elizabeth (Palgrave Macmillan, 2025)
We propose a novel framework that complements the extant literature by contextualizing blockchains’ impact on financial reporting functions. The framework is based on two theories—diffusion of innovation theory and norm lifecycle theory—and reflects differing stages of the norm adoption lifecycle. We highlight the difficulty of blockchains being effective without the development of proper norm legitimacy (since norms are not yet established). We clarify that, at the infrastructure level, the diffusion of blockchain technology for financial reporting is bound by two key limitations: (1) a limitation of scope and (2) a limitation of discretion. We argue that these limitations may or may not prevent blockchain technology’s adoption, and that its further diffusion with central governance support can facilitate decentralized blockchain infrastructure within the broader digital ecosystem. We posit that blockchains can be obsolete, sustaining, or disruptive for the accounting profession, depending on when and where in the lifecycle they are adopted. Our research has implications for policymakers, regulators, and governance in terms of blockchain technology diffusion and its influence on financial reporting functions.
Keywords: decentralized ledger technology; digitalization; blockchains; accounting; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|